PROBLEMATIKA PEMBELAJARAN INSYA’ TAHRIRI DALAM PERSPEKTIF TEORITIS - Dicky Herlambang; Anwar Sidik (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2026)
This study aims to examine the problems of Insya’ Tahriri learning from a theoretical perspective. Insya’ Tahriri is an Arabic writing skill that requires mastery of grammatical rules (nahwu and sharaf) as well as the ability to develop ideas in written form. However, in practice, this learning often encounters various difficulties that affect students’ writing performance.This research uses a library research method by collecting data from relevant books, journals, and scientific articles. The data collection technique is conducted through documentation study, while the data analysis is carried out using a descriptive-analytical approach by reviewing theories related to Insya’ Tahriri learning.The results of the study indicate that the main problems in Insya’ Tahriri learning include students’ low mastery of Arabic grammar, limited vocabulary, difficulties in sentence construction, and weak ability to develop ideas in writing. In addition, less varied teaching methods also contribute to students’ low writing achievement.In conclusion, Insya’ Tahriri learning still faces several theoretical and practical challenges. Therefore, the application of more varied teaching methods, continuous writing practice, and strengthening of grammar and vocabulary mastery are needed to improve students’ Arabic writing skills effectively.